The Predictive Value of Impulsivity and Risk-Taking Measures for Substance Use in Substance Dependent Offenders - Rieser, Nathalie M.; Shaul, Lilach; Blankers, Matthijs; Koeter, Maarten W. J.; Schippers, Gerard M.; Goudriaan, Anna E. (Frontiers in Behavioral Neuroscience, 2019)
Impulsivity and risk-taking are known to have an important impact on problematic substance use and criminal behavior. This study examined the predictive value utility of baseline self-report and behavioral impulsivity and risk-taking measures (Delay Discounting Task, Balloon Analogue Risk Task and Behavioral Inhibition, Behavioral Activation Scale (BIS/BAS)) in 12-months follow up substance use outcomes (e.g. use of alcohol, cannabis and other substances) and criminal recidivism (yes/no). Participants were 213 male offenders with a substance use disorder (SUD) under probation supervision. Predictors with a (nearly) significant association (p < 0.10) in the bivariate analyses were combined with substance use at baseline in a multiple regression analysis. Bivariate regression analyses showed that BIS and BAS levels were associated (respectively) with the use of alcohol and cannabis. Multiple regression analysis showed that BIS was negatively associated with alcohol use at follow-up, whereas cannabis use at baseline and BAS predicted cannabis use at follow-up. At a trend level, interactions between delay discounting and risk taking, and interactions between baseline cannabis use and BAS and risk-taking (BART) predicted cannabis use at follow-up, Other substance use at follow-up was solely predicted by baseline other substance use. Overall, the findings provide only a marginal support for the predictive utility of impulsivity and risk-taking in accounting for variability in substance use among offenders with a SUD. This may be partly explained by the fact that only a limited number of psychological factors was assessed in this study. The studied population consists of a severe group, in which relapse into substance use or criminal behavior likely is related to complex, interacting biopsychosocial factors, of which impulsivity measures play a relatively small part.